Penggunaan Lensa Kontak untuk Astigmatisma Paska Keratoplasti - Tri Rahayu (Majalah Oftalmologi Indonesia, 2015)
Background: Fitting Contact Lenses for post penetrating keratoplasty patiens can be a great challenges to contact lens practitioner. Despite advances in surgical techniques for penetrating keratoplasty, post- operative ametropia and high irregular astigmatism still remain common. Patients who have such those problems may need contact lenses to achieve optimal vision.Case Illustration: Case 1. A 12 years old boy have a high myop and astigmatism after undergone penetrating keratoplasty combined with traumatic cataract extraction and IOL implantation. His right eye vision was 6/24 with corrections of S – 8.00 C – 6.50 x 150. His right eye was fitted with RGP contact lens with Base curve of 7.20 mm, Power of – 10.25 D, and diameter of 8.80 mm. His RE vision with RGP contact lens was 6/12; Case 2. Female, 18 years old, was diagnosed with compound high myopia astigmatism of right eye due to disfigured cornea post keratoplasty and high astigmatism of the left eye due to corneal scar. Piggyback contact lens system is then used to treat her right eye.The patient’s uncorrected visual acuity on the right eye was half meter counting finger, became 6/40 with spectacle and 2 meters counting finger became 3/60 with spectacle on the left eye. With piggyback contact lens consisting of soft contact lens 8.60/-10.00/14.20 and RGP lens 7.20/-4.00/8.8 on the right eye, and RGP lens 7.90/-5.00/9.2 on left eye, her visual acuity became 6/12 on her right eye became 6/9 on the left eye.Conclusion: Rigid gas-permeable and combination of rigid gas permeable and soft contact lenses can be fitted with piggy-back system successfully in patients unable to achieve optimal vision with spectacle correction after penetrating keratoplasty